Thermoresponsive hydrogels from poly(ethylene glycol)-based graft poly(dimethyl siloxane) amphiphilic copolymers with tunable lower critical solution temperatures - Roman, Stacey Kelly (Stellenbosch : Stellenbosch University, 2021, 2021)
Thesis (MSc)--Stellenbosch University, 2021.